(untitled) (REMUNOM, 2025)
This article investigated the perception of employees of the Federal University of Espírito Santo (UFES) about the Retirement Preparation Program (PPA), implemented between 2017 and 2021, in three dimensions: health and autonomy, occupation and post-career, and social support. The survey method was used with convenience sampling, whose data were collected through semi-structured interviews and analyzed through content analysis. The results indicated that a) there is a lack of financial planning for retirement, b) encouragement to practice healthy habits, c) preparation for post-career occupation was praised, and d) the respondents value the social support network. The conclusion shows that the retirement program studied is considered essential and relevant as a people’s well-being policy for the participants. The main contribution of this study to science is the confirmation that retirement programs based on psychosocial principles and well-being allow a reduction in negative aspects of this period, such as depression, anxiety, and isolation.